CHARISMATIC LEADERSHIP STYLE OF KIAI IN PONDOK PESANTREN LIRBOYO KEDIRI - Bagus Ahmadi (PT. Media Akademik Publisher, 2024)
This study aims to analyse the influence of Kiai's charismatic leadership style at Pondok Pesantren Lirboyo Kediri on the motivation, participation, and literacy strengthening of santri. Although many studies have discussed charismatic leadership in an educational context, research on its specific impact on the educational environment in pesantren, particularly in the context of literacy, is limited. Based on the questionnaire results, 96.7% of the pesantren residents felt that Kiai has the ability to motivate and mobilise all members of the pesantren to participate in educational and social activities. This finding shows that Kiai's leadership acts as an inspirer that encourages active involvement among santri and administrators. Furthermore, 98.3% of respondents agreed that Kiai has a clear vision and goals in his leadership, which has an impact on the motivation of santri to learn and contribute. In the context of literacy, Kiai's leadership style has proven effective in strengthening santri's understanding of literacy values, both academic and social. Finally, around 93.3% of respondents agreed that Kiai wants to create positive changes in the pesantren, which shows hope and belief in innovation and improvement in educational aspects. This research confirms that Kiai's charismatic leadership not only increases santri motivation and participation but also strengthens literacy as an important element in their character building and social intelligence.